Diversidade taxonômica e funcional de aves dispersoras em áreas de regeneração natural pós-mineração - AMARAL, Lia Torres (2022)
Anthropogenic disturbances in natural habitats can lead to complex ecosystem changes and even loss of biodiversity. Faced with such changes, the restoration of ecosystems is essential to help reestablish the community and the levels of diversity prior to disturbance. Seed dispersal is one of the ecological functions that can greatly contribute to forest succession, and birds are important dispersing agents as they can allow the entry of seeds into degraded fragments of tropical regions. Therefore, this work aims to evaluate the taxonomic and functional diversity of potentially dispersing understory birds in an area of natural post-mining regeneration. Data were collected in the municipality of Paragominas, in the natural regeneration areas (RN) and in the forest fragments (FF) of the company Mineração Paragominas SA. Mist nets were placed in the understory of nine areas of RN and FF, which captured 40 potentially dispersing bird species. The results showed that the species composition differed, and forest fragments had more diet specialist species, probably due to the stratification of the environment, while areas in natural regeneration having more generalist species. The taxonomic diversity did not diverge between areas, but this may mask a turnover from specialist to generalist species that adapt better to the environment, or an influence of the sampling effort. The natural regeneration areas had a greater functional diversity and species richness than the forest, and this may be linked to the fact that the vegetation of a secondary forest can provide important resources for nesting, foraging and protection for birds, which tends to attract wide variety of taxa. The results highlight how different measures of diversity can present different responses of birds to changes in the environment, which emphasizes the importance of considering multiple aspects when analyzing biodiversity. Furthermore, it emphasizes the importance of forests in the process of regeneration, as they may become even more important in the future, as ways of safeguarding the existence of species in some regions.